Evaluation of Textile Electrodes for Electrotherapy - Loosberg, B.; Werner, T.; Smolenski, U. C. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2012)
This study evaluates the suitability of new textile electrodes manufactured by Textilforschungsinstitut Thüringen-Vogtland e. V. (TITV).This open, controlled trial included 25 healthy young volunteers. New textile electrodes and conventional adhesive electrodes were compared. Therefore, transcutaneous electrical nerve stimulation (TENS), medium-frequency neuromuscular electrical stimulation (NMES), and EMG-triggered stimulation was conducted on the participant’s thighs. The discomfort experienced was rated on the visual analogue scale (VAS). Change in skin resistance level (SRL), skin temperature and pain pressure threshold (PPT) was measured. The current intensity used for effective stimulation was noted, and the participants were asked for their preferred type of electrodes.Initially, textile electrodes are less comfortable and SRL and skin temperature are lower. The changes in surrogates, if present, do not differ between textile or adhesive electrodes.The textile electrodes evaluated in this study can generally be used for TENS, NMES, and EMG biofeedback therapy. To allow proper stimulation, the electrodes have to be wetted and applied with pressure.Wetting and applying with pressure are disadvantages that should be improved in further prototypes.
Keywords: textile electrodes; adhesive electrodes; electrical stimulation; biofeedback